Seth L. Haarrabee, The Charter and Ordinances of the City of Portland, Maine 136 (1892) - (:unkn) unknown (My University, 1892)
§ 4: No person shall sell to any child under the age of sixteen years, without the written consent of a parent or guardian of such child, any blank cartridge, or any pistol, or mechanical contrivance specially arranged or designed for the explosion of the same and any person violating the provisions of this ordinance shall be liable to a penalty of not less than fifty, and not exceeding one hundred dollars, to be recovered on complaint to the use of the City of Portland.
Keywords: TRANSFER - MINORS